Sorry to bother you [videorecording (DVD)] - Stanfield, LaKeith, 1991-; Thompson, Tessa, 1967-; Fowler, Jermaine (Twentieth Century Fox Home Entertainment, 2018)
In an alternate present-day version of Oakland, telemarketer Cassius Green discovers a magical key to professional success, propelling him into a macabre universe.